Investigation of x-ray emission from high-current discharges of the PF type - Skladnik-Sadowska, E.; Sadowski, M.J.; Malinowsk, K.; Surala, W.; Zaloga, D.; Paduch, M.; Zielinska, E.; Tomaszewski, K. (Вопросы атомной науки и техники, 2016)
The invited paper reports on measurements of soft x-rays emitted from hot plasmas produced in a modernised PF-1000U facility. The discharges were performed at the D2-filling with or without a Ne-admixture, under the initial pressure of 0.9 or 1.5 Torr and at the initial charging voltage equal to 16 or 18 kV. Time-integrated x-ray images were recorded with a pinhole camera situated side-on, at an angle of 75º to the z-axis. Differences in the pinch column structure were observed. Time-resolved measurements were performed with four PIN diodes located behind filtered pinholes. Two couples of PIN diodes (with Be-filters of 7 and 10 μm in thickness) observed 30 mm-diam. regions which had centres at a distance of 30 and 60 mm form the electrode outlets. From the recorded timeresolved x-ray signals the electron temperatures (Te) were calculated. For the pure D2-discharges the estimated Te values ranged from 75 to 250 eV depending on the discharge conditions. For discharges with a Ne-admixture Te values were higher and reached about 800 eV.